Morphotropic Phase Boundary Region 0.7BiFeO3-0.3BaTiO3 Ceramics Exploration Under the Influence of the Incorporated Sn-Ions for Piezo/Ferro Applications - Ahmad Hussain; Nawishta Jabeen; Imtiaz Ahmad Khan; Muhammad Usman Khan; Muhammad Adnan Qaiser; Zaki I. Zaki; Mohamed E. Khalifa (Crystals)
In the field of piezoelectric applications, perovskite-based multifunctional composite ceramics are widely explored. The morphotropic phase boundary (MPB) regions, where dual structural phases coexist, play a crucial role in boosting the ferroelectric and piezoelectric properties significantly. Herein, MPB-region-existent 0.7BiFeO3-0.3BaTiO3 (BFBT) composite ceramic is investigated under the influence of wt%Sn-ion incorporation at the lattice sites of the BFBT. Specifically, the ceramic composition BFBT:0.2Sn has demonstrated excellent remnant polarization (Pr ~ 22.68 µC/cm2), an impressive piezoelectric coefficient (d33 ~ 211 pC/N), stable impedance of 1.07 × 107 Ω, a Curie temperature of 435 °C and low dielectric loss (tanδ) of <0.5. Moreover, the BFBT:0.2Sn ceramic has also maintained a stable d33 of ~150 pC/N and resistivity of ~102 Ω even at a temperature of 400 °C. Such outcomes confirm the ability and potential of the BFBT:0.2Sn ceramic composition for high-temperature piezoelectric applications.